Create, share and learn. Experiences with free software, free culture and collaboration in formal and non formal education in Colombia (2012)
New media technologies, specially software have been of great impact in modern society.The combination of computer/software/networks as creative machines is present in everyday life. This article is focused in this interactions specially from the perspective of free open source software (FOSS). In doing so, the influence of its values is traced from the original hacker culture ethics to the free software four freedoms, showing a software explained culture as in the software studies disciplines. Also the bazaar creation model is explained, as a metaphor originally intended to software development that now is present in several realms as the open source method can be applied in diverse fields. To the education field, this values are seen as encouraging of the remix and amateur culture, producing engaging methods to education through media manipulation. For this reasons remix culture and temporary autonomous zones are explained as extensions of the bazaar model to educational related fields. Finally to summarize, examples from non formal and formal (University) education in Colombia are presented, where the create and share approach can be seen in action. This examples were explored from a participant perspective. Finally some conclusions and recommendations are made, as a result of a critical assessing of the ideas presented.